Tracking novelties in psychotherapy process research: The innovative moments coding system - Gonçalves, Miguel M. (2011)
This article presents a method for the assessment of innovative moments, which are novelties that emerge in contrast to a client's problematic self-narrative as expressed in therapy, the innovative moments coding system (IMCS). The authors discuss the theoretical background of the IMCS as well as its coding procedures. Results from several studies suggest that the IMCS is a reliable and valid coding system that can be applied to several modalities of psychotherapy. Finally, future research implications are discussed.